Modelling the risk of professional disengagement from a cohort study of 181,676 workers in the south of France - Gauthier Bellagamba; Vincent Houtin; Anne Landi; Marie-Pascale Lehucher-Michel (PLoS ONE, 2026)
Objective This study determines a set of medical, occupational, and social risk factors of professional disengagement that can be documented early in occupational health practice. Method This study was carried out on a cohort of French workers. Data were extracted from computerised occupational health medical follow up records. The professional disengagement risk was assessed by healthcare professionals. Logistic regression models were applied. Results 181,676 workers were included. Of these, 4.05% had a high professional disengagement risk index (PDRI) and 13.0% a moderate risk. Women (OR: 1.21) and 50–61-year-old (OR: 5.17) workers appear to be the most at high risk. White-collar (OR: 1.63) and blue-collar (OR: 1.60) have a higher at risk compared with manager. The main disorder risk factors of high PDRI were mental disorders (OR: 8.79), musculoskeletal disorders including shoulder (OR: 6.23), arm (OR: 3.80), or hand (OR: 3.21) and kidney disorders (OR: 5.57). Recognition of a professional disengagement (OR: 7.55) or long/iterative sick leave (OR: 5.08) is associated with high PDRI. Occupational exposure associated with high PDRI include “poor interpersonal relationships” (OR: 6.05), “job insecurity” (OR: 4.14) and “conflicts of values” (OR: 3.88). Exposure to noise (OR: 1.33) and heavy work (OR: 1.25) are associated with a high PDRI, however some physical exposures appear to be ‘protective’ such as lower limb postures (OR: 0.68) or whole-body vibrations (OR: 0.64). Conclusions Mental and musculoskeletal disorders, poor working relationships, job insecurity and conflicts of values all appear to be avoidable risk factors for professional disengagement These results reinforce the importance of targeted prevention and orientates future research to refine the accuracy of the variables and better distinguish gradients and thresholds of risk. What is already known Numerous studies have investigated the factors facilitating or limiting a return to work after professional disengagement. What this study adds This study highlights the medical and professional factors which should be early documented to prevent professional disengagement.